Metabolic characterization and antioxidant activity in sweet cherry (Prunus avium L.) Campania accessions: Metabolic characterization of sweet cherry accessions. (1st February 2018) - Mirto, Antonio; Iannuzzi, Federica; Carillo, Petronia; Ciarmiello, Loredana F.; Woodrow, Pasqualina; Fuggi, Amodio
Highlights: 43 Accessions of sweet cherry from Campania region were characterized. Evaluation of AsA, GSH, tocopherols, anthocyanins, poyphenols, H2 O2 and MDA. Evaluation of PODs, PPOs and APX enzymes. Selection of accessions suitable for long post-harvest storage. Abstract: The failure of the antioxidant scavenging system in advanced ripening stages, causing oxidative stress, is one of the most important factor of fruit decay. Production of rich antioxidant fruit could represent a way to delay fruit senescence and preserve its characteristics. We investigated the antioxidant metabolites (ascorbate, glutathione, tocopherols, and polyphenols) and enzymes (ascorbic peroxidases, peroxidases and polyphenol oxidases) involved in the antioxidant response in forty-three accessions of sweet cherry fruits from Campania region. Our results highlight accessions with high antioxidant metabolites contents but low enzymatic activities. These represent important factors in both pre- and post-harvest on the qualitative and nutritional characteristics of sweet cherry. Observed differences are probably due to endogenous characteristics making these accessions particularly interesting for breeding programs aimed to improve fruit quality and shelf-life and for addressing the cultivation of a specific characterized cultivar based on the intended use, fresh consumption or processed products.